Removal of methane through hydrological, microbial, and geochemical processes in the shallow sediments of pockmarks along eastern Vestnesa Ridge (Svalbard) - Wei‐Li Hong; Simone Sauer; Giuliana Panieri; William G. Ambrose; Rachael H. James; Andreia Plaza‐Faverola; Andrea Schneider (Limnology and Oceanography, 2016)
The recent discovery of methane seeps in the Arctic region requires a better understanding of the fate of methane in marine sediments if we are to understand the contributions of methane to Arctic ecosystems and climate change. To this goal, we analyze pore water data from five sites along eastern Vestnesa Ridge, a sediment drift off‐north‐west Svalbard, to quantify the consumption of dissolved methane across the sulfate‐methane‐transition‐zone which are 3–5 m below seafloor from the investigated sites. We use transport‐reaction models to quantify the hydrology as well as the carbon mass balance in the sediments. Pore water profiles and our model results demonstrate that hydrological, microbial, and geochemical processes/reactions efficiently remove methane carbon from fluid over different time scales. We interpret the nonsteady‐state behavior of the first 50–70 cm of our pore water profiles from the active sites as an annual scale downward fluid flow due to a seepage‐related pressure imbalance. Such downward flow supplies sulfate which enhances methane consumption through anaerobic oxidation of methane (AOM) within this depth range. Our steady‐state modeling confirms the efficiency of AOM in consuming dissolved methane in the upper 0.8–1.2 m of sediments. Based on the phosphate profiles, we estimate that AOM at the active pockmarks may have been operating for the last two to four centuries. Precipitation of authigenic carbonate removes more than a quarter of the dissolved inorganic carbon produced by AOM and fixes it as authigenic carbonate in the sediments, a process that sequestrates methane carbon over geological time.